Impact of hormone therapy on the bone density of women with premature ovarian insufficiency: A systematic review. (January 2023) - Costa, Giulia Paiva Oliveira; Ferreira-Filho, Edson Santos; Simoes, Ricardo dos Santos; Soares-Junior, José Maria; Baracat, Edmund Chada; Maciel, Gustavo Arantes Rosa
Highlights: Women with premature ovarian insufficiency tend to have lower bone mineral density. Hormone therapy can improve the bone health of women with premature ovarian insufficiency. Delay in the diagnosis can negatively influence treatment effectiveness in maintaining bone mass or restoring it to the normal range. Higher doses of estrogen, with at least 2 mg estradiol or 1.25 mg conjugated equine estrogens, could better prevent bone loss in this population. Abstract: Introduction: Women with premature ovarian insufficiency (POI) are exposed to a long period of estrogenic deficiency, which potentially brings higher health risks, especially regarding bone health. We performed a systematic review of the literature to evaluate the effect of hormone therapy (HT) on bone mineral density (BMD) in women with POI. Materials and methods: A systematic search was performed of the MEDLINE and EMBASE databases up to September 2021. We included studies that analyzed women with idiopathic (spontaneous) POI treated with HT, and those who had BMD evaluated. Analysis of risk of bias of studies selected was performed. Results: We found 335 articles and selected 16 studies according to the inclusion criteria. Most of the studies revealed lower bone density in both the femoral neck and lumbar spine of women with POI compared with healthy women. Bone mass had the tendency to remain stable in women treated with estrogen + progestin therapy. However, in women already with bone mass loss, the therapy - in the doses most frequently used - was not able to revert the loss. Higher doses of estrogen seem to have a positive impact on BMD, as did combined oral contraceptives used continuously. Also, the interruption of HT for longer than one year was linked to significant bone loss. Conclusion: Although HT brings clear benefits, further studies are needed to establish its long-term effects, as well as doses and formulations with better protective effects on the bone mass of these women.